The Influence of Brand Equity and Brand Trust on E-Commerce Consumer’s Loyalty (Zalora Consumer Research) - Putra, Dennis Mahendra; Sin, Liem Gai (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
This research aims to analyze the influence of brand equity and brand trust on e-commerce consumer’s loyalty. This research is also titled as hypothesis test research which undertaken test on hypothesis with Zalora’s consumer in Malang city as a source of this research. Data analysis method used multiple linear regressions with variable t and variable t. The result shows that brand equity and brand trust have an influence on Zalora’s consumer loyalty. It indicates that the increasing of brand trust followed by increasing of consumer’s loyalty.